1998
DOI: 10.1007/s004410051015
|View full text |Cite
|
Sign up to set email alerts
|

Differential myogenicity of satellite cells isolated from extensor digitorum longus (EDL) and soleus rat muscles revealed in vitro

Abstract: Following muscle damage, fast- and slow-contracting fibers regenerate, owing to the activation of their satellite cells. In rats, crush-induced regeneration of extensor digitorum longus (EDL, a fast muscle) and soleus (a slow muscle) present different characteristics, suggesting that intrinsic differences exist among their satellite cells. An in vitro comparative study of the proliferation and differentiation capacities of satellite cells isolated from these muscles is presented there. We observed several diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
2
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(83 citation statements)
references
References 46 publications
(48 reference statements)
4
75
2
2
Order By: Relevance
“…Among these cells were probably inflammatory ones, as our technique of satellite cells isolation does not exclude non-myogenic cells. The presence of such cells, of which not all were capable of myogenic differentiation, has been demonstrated by others using the same isolation technique [35].…”
Section: Molecular Changes Accompanying Regeneration After Mechanicalmentioning
confidence: 70%
See 1 more Smart Citation
“…Among these cells were probably inflammatory ones, as our technique of satellite cells isolation does not exclude non-myogenic cells. The presence of such cells, of which not all were capable of myogenic differentiation, has been demonstrated by others using the same isolation technique [35].…”
Section: Molecular Changes Accompanying Regeneration After Mechanicalmentioning
confidence: 70%
“…Slow-twitch muscle regeneration has been shown to be impaired compared to fasttwitch muscle [19,20]. Furthermore, cells isolated from different muscles have been shown to express different myogenic potential [11,35]. Another variable is associated with the choice of mouse strain.…”
Section: Methods Of Muscle Injury Influences the Process Of Muscle Regmentioning
confidence: 99%
“…Indeed, individual evaluations of satellite cells by clonal analysis are necessary to determine whether all satellite cells retain stem cell functions. Clonal analysis has demonstrated that proliferation ability varies widely among satellite cell clones in muscle [22][23][24] . Analysis of the range of satellite cell behaviours on a "per myofibre" basis has revealed that there is a large range of proliferative potential among satellite cell clones from the same myofibre in the EDL 13) .…”
Section: Satellite Cell Heterogeneity Within Fibresmentioning
confidence: 99%
“…However, longer durations of differentiation can lead to myotube detachment and subsequent cellular death. Moreover, it has been shown in rats that the source of skeletal muscle biopsy (that is, soleus compared to extensor digitorum longus) affected the rate at which the isolated cells differentiated (Lagord et al, 1998). This suggests that the source of muscle will alter the myogenic properties of the derived human primary myotubes.…”
Section: Variable Expressionmentioning
confidence: 99%